Hunters. David Chancellor. Schilt Publishing Amsterdam, 2012 - Van Damme, Patrick (Afrika Focus, 2014)
Hunters is an arresting exploration of tourist trophy hunting in southern Africa. It is not difficult to appreciate the beauty of the pictures and their settings. But it is difficult to agree with the book’s thematic. Primarily relying on portraiture, both in the field and in the hunters’ homes and trophy rooms, Chancellor delves into a controversial and lucrative subculture. Despite the fact that his camera never shies away from blood, the gore is at a notable minimum. Instead, the tension that fills each frame is drawn from his subjects – the foreign hunters, their families, the local guides and the very land to which they have come seeking their prey. One can see the pride, the glee, the almost orgiastic facial expressions resulting from the kill. This is the hunter feeling her/himself to be on top of the world, at the apex of creation. S/he decides. S/he kills. A show of supremacy over nature. Most pictures speak for themselves. Even though Chancellor does not take a position (it seems he never hunted himself ), it should be clear from the images that there is little pride to be taken from killing these animals. Trophy hunting is a small-scale massacre. Every animal killed is a decrease in its population. Full stop. I know there are people who argue that hunting, and trophy hunting more specifically, helps to control wildlife, that it helps to maintain much-needed and often precarious equilibria. Chancellor seems to think that trophy hunting would appear to be a more sustainable and environmentally friendly way of wildlife control than ‘mere’ hunting for fun. Populations are monitored and local communities survive on the income they earn from tracking, and accompanying the white hunters. But at the end of the day hunting is and remains a brutal, inhumane activity. While the pictures do convey the brutality to some degree, they also express an aesthetic that is scenic and beautiful.